The Effect of Electronic Word of Mouth in Social Media and Experiential Value on Destination Image Dan Revisit Intention after Earthquake in Lombok (Global Journal of Management and Business Research, 2020)
Abstract not found
Keywords: ewom; destination image; experiental value; revisit intention